An explorative study of Congolese "bouncers" in Cape Town: constructing masculine identities in liminal spaces - Harris, Kirsten (Department of Public Law, 2017)
The intended purpose of the following thesis was to explore and attempt to understand how Congolese Bouncers, specifically in Cape Town, construct their own masculine identities in liminal spaces. This exploration entailed examining the complexities and connections between immigrants, immigrant bouncers and masculine identities; within those areas, encompassing a multitude of periphery factors. The literature reviewed for this thesis then encompassed research on immigrants in South Africa, masculinities and masculine identities, bouncers, and illegal substances; individually as well as the correlations between and amongst the different areas. Thus, the following thesis consists of five chapters, with three, identified, key themes set out in individual chapters. A Foucauldian framework was used as a means of synthesising the often divergent areas of thought, as, at their core, they share concerns with knowledge, power, violence (in various forms) and identity. In the attempt to understand the subjective experiences and realities of these Congolese bouncers, the methodology employed for the collection of data was entirely qualitative in nature; specifically, that of phenomenological research. This method was situated within the (social) constructivist paradigm, used to guide the researcher in understanding "a phenomenon from the perspective of those experiencing it" (Constantino, 2008:119); using participant observation and interviewing as the primary forms of data collection. Upon listening to the individual "stories" and lived realities of the research participants, one of the key understandings in the conclusion of this thesis is that the "immigrant bouncer", in a South African context, exists in different realities. His identity, and more specifically his construction of masculinity, is divided by necessity between day and night. An identity that is constantly shifted and adapted to unfixed social structures. Through this research the hope is to create space for an alternative discussion which disrupts current conceptions around both immigrants and bouncers.